Geometría monumental del poder maya: el caso de Oxkintok - Rivera Dorado, Miguel (Revista Española de Antropología Americana, 2007)
This article searchs the relationships between the architecture of the Maya cities, their formal characteristics and symbolism, and the notion of state in the patterns of cultural and political evolution. The model is the site of Oxkintok, where the archaeological excavations is performed in the last twenty years.